The impact of teacher emotional support on learning engagement among college students mediated by academic self-efficacy and academic resilience - Wenjing Guo; Juan Wang; Na Li; Luxin Wang (Scientific Reports)
Abstract College students’ learning engagement not only significantly influences their academic performance but also plays a vital role in their future career development. Ensuring that students maintain high levels of engagement is essential for society’s goal of cultivating high-quality talent. Therefore, understanding the key factors that drive student engagement is critical for educators as they develop effective strategies to foster this engagement. This study aims to explore the mechanisms behind the relationship between teachers’ emotional support and college students’ learning engagement, with a focus on the mediating roles of academic self-efficacy and academic resilience. Accordingly, the following hypotheses are proposed: (1) Teacher emotional support positively predicts learning engagement; (2) Academic self-efficacy and academic resilience serve as mediators between teacher emotional support and learning engagement; (3) Academic self-efficacy and academic resilience function as sequential mediators in the relationship between teacher’ emotional support and learning engagement. This study utilized a random sampling method to survey 414 eligible college students from a university in western Shandong Province, China. Standardized scales were employed to measure teacher emotional support, learning engagement, academic self-efficacy, and academic resilience. For data analysis, Pearson correlation analysis was performed first, followed by the bias-corrected percentile Bootstrap method. (1) The study detected no significant systematic bias, and the correlations among teacher emotional support, learning engagement, academic self-efficacy, and academic resilience were all statistically significant. (2) Grounded in Self-Determination Theory, this study clarifies the relationship between teacher emotional support and learning engagement. The findings reveal that teacher emotional support positively predicts academic self-efficacy, academic resilience, and learning engagement. Similarly, both academic self-efficacy and academic resilience positively predict learning engagement, with academic self-efficacy also directly and positively predicting academic resilience. Notably, all proposed hypotheses were empirically supported. (3) The indirect effect through academic self-efficacy is 0.085, while the indirect effect through academic resilience is 0.121. Additionally, the combined indirect effect of both academic self-efficacy and academic resilience as sequential mediators is 0.059. (4) The cumulative total of all these indirect effects is 0.265. Based on Self-Determination Theory, we propose a sequential mediation model where teachers’ emotional support significantly and positively impacts students’ learning engagement, with academic self-efficacy and academic resilience acting as key mediators in this relationship. Additionally, teachers’ emotional support enhances students’ learning engagement by boosting their academic self-efficacy and reinforcing their academic resilience. These findings offer strong theoretical support for educational practice.